Computational Intelligence for Biometric Applications: a Survey - Donida Labati, Ruggero; Genovese, Angelo; Muñoz, Enrique; Piuri, Vincenzo; Scotti, Fabio; Sforza, Gianluca (International Journal of Computing, 2016)
Biometric systems consist of devices, procedures, and algorithms used to recognize people based on their physiological or behavioral features, known as biometric traits. Computational intelligence (CI) approaches are widely adopted in establishing identity based on biometrics and also to overcome non-idealities typically present in the samples. Typical areas include sample enhancement, feature extraction, classification, indexing, fusion, normalization, and anti-spoofing. In this context, computational intelligence plays an important role in performing of complex non-linear computations by creating models from the training data. These approaches are based on supervised as well as unsupervised training techniques. This work presents computational intelligence techniques applied to biometrics, from both a theoretical and an application point of view.